2008
DOI: 10.1016/j.ijinfomgt.2008.01.007
|View full text |Cite
|
Sign up to set email alerts
|

User perceptions of online public library catalogues

Abstract: Online Public Library Catalogues (OPACs) are widely used electronic library catalogues giving a wealth of remote access to library information resources. Users should be involved early in the OPAC development cycle process in order to ensure a usable and functional interface, as the integration of user-defined requirements of OPACs, along with the other Human-Computer Interaction considerations, offer a better understanding of user perceptions and expectations respect of OPACs, ultimately resulting in truly us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 19 publications
0
14
1
1
Order By: Relevance
“…A large body of work has investigated general search behaviors and processes [1,13,25], and, more specifically, search processes in library catalogs (e.g., [4,10,18,23,27,42]), public libraries [30,36,37,38], and book stores [7]. When designing our in-situ search system, we followed designcentered models of the search process [40], as well as contemporary guidelines toward designing search interfaces [16,46].…”
Section: Designing (Library) Search Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of work has investigated general search behaviors and processes [1,13,25], and, more specifically, search processes in library catalogs (e.g., [4,10,18,23,27,42]), public libraries [30,36,37,38], and book stores [7]. When designing our in-situ search system, we followed designcentered models of the search process [40], as well as contemporary guidelines toward designing search interfaces [16,46].…”
Section: Designing (Library) Search Interfacesmentioning
confidence: 99%
“…Early studies found that while targeted, known-item searches are well-supported, open-ended subject searches are problematic [2,26,29,45]. More recent studies confirm that this still holds true: people still often find OPAC interfaces difficult to use, in particular compared to canonical web search engines which support more free-form queries [18,23]. Studying book search strategies in public libraries, Mikkonen and Vakkari found the catalog to be the least popular tactic [30].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the OPACs (Online Public Access Catalogs; see Kani-Zabihi et al (2008) for a treatment from about the time of RI1 design) established in the library community, while comparable for the purpose of locating information resources, could not efficiently address the use cases, and no broadly accepted standard for client, rather than user, interfaces to OPACs, lent itself to adoption by the VO community.…”
Section: Historymentioning
confidence: 99%
“…92 The British Library's desire "to provide a system for real users" 93 in their development of the OPAC'97 led them to break with tradition and transfer project management away from the IT department to one centered on user services. This shift was phrased in terms of favoring a methodology that understood the problems and requirements of users over one that concentrated on delivering a reliable, timely system on budget.…”
Section: Wilsonmentioning
confidence: 99%